PENGARUH PERPUTARAN AKTIVA DAN RETURN ON ASSETS TERHADAP PERTUMBUHAN LABA ( Studi empiris pada Laporan Keuangan PT. Unilever Indonesia, Tbk dari Tahun 2004 sampai Tahun 2018) - Rahmat Hidayat (JURNAL BISNIS dan TEKNOLOGI, 2019)
This study is to determine the effect of asset turnover and return on assets on earnings growth and the object under study is the financial statements of PT. Unilever Indonesia, Tbk from 2004 to 2018. The research methods used were verification and quantitative methods. The variables studied were asset turnover and return on assets as the independent variable and earnings growth as the dependent variable. This data was analyzed using multiple linear regression with the help of SPSS 18 for Windows. The results of this study indicate that simultaneous asset turnover and return on assets influence earnings growth significantly and have a correlation at strong intervals. Correlation has a positive value indicating that the relationship between asset turnover and return on assets to earnings growth is unidirectional. The magnitude of the effect of asset turnover and return on assets on profit growth of 41.5% while the remaining 58.5% is influenced by other variables not examined.